DETERMINATION OF THE QUALITY OF VEGETABLE OILS - Барус, Маріанна; Скрипська, Ольга; Білокопита, Галина (SWorldJournal, 2023)
The article examines the organoleptic, physico-chemical quality indicators of five samples of sunflower and olive oil, qualitative tests were conducted for the presence of wax, wax-like substances and soap in all samples of the studied oils.